Islamic Religious Education And Modern Islamic Culture In Prevention Of Radicalism At Buana Perjuangan Karawang University - Ainur Alam Budi Utomo; Zainal Abidin Muhja (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This research aims to identify and study the spread of radicalism and terrorist teachings in Universitas Buana Perjuangan, Karawang.This literary descriptive research is a qualitative study with analytical approach that tackles the spread of radical techings in Universitas Buana Perjuangan, Karawang. The respondents include students and stakeholders both in the university and in the foundation as well. It is expected to prevent the spread of radical teachings in Universitas Buana Perjuangan, Karawang and to provide policy recommendations to the university’s stakeholders through Islamic education and introducing modern Islamic culture.